Theoretical research of construction parameters of the upper support of spinning machine spindle - Войтович, Ольга Андриановна (Eastern-European Journal of Enterprise Technologies, 2012)
A formula, determining dependence of coefficient of friction of sulky at the ring of spindle of spinning machine from the vibration of spindle, is in-process shown out. The coefficient of friction is expected at other equal terms of leadthrough of research